Frequency of diabetes and other comorbidities in chronic inflammatory demyelinating polyradiculoneuropathy and their impact on clinical presentation and response to therapy. Issue 10 (31st August 2020) - Doneddu, Pietro Emiliano; Cocito, Dario; Manganelli, Fiore; Fazio, Raffaella; Briani, Chiara; Filosto, Massimiliano; Benedetti, Luana; Bianchi, Elisa; Jann, Stefano; Mazzeo, Anna; Antonini, Giovanni; Cosentino, Giuseppe; et al.
Abstract : Objectives: To determine the prevalence of different comorbidities in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), and their impact on outcome, treatment choice and response. Methods: Using a structured questionnaire, we collected information on comorbidities from 393 patients with CIDP fulfilling the European Federation of Neurological Societies and Peripheral Nerve Society criteria included in the Italian CIDP database. Results: One or more comorbidities were reported by 294 patients (75%) and potentially influenced treatment choice in 192 (49%) leading to a less frequent use of corticosteroids. Response to treatment did not differ, however, from that in patients without comorbidities. Diabetes (14%), monoclonal gammopathy of undetermined significance (MGUS) (12%) and other immune disorders (16%) were significantly more frequent in patients with CIDP than expected in the general European population. Patients with diabetes had higher disability scores, worse quality of life and a less frequent treatment response compared with patients without diabetes. Patients with IgG-IgA or IgM MGUS had an older age at CIDP onset while patients with other immune disorders had a younger age at onset and were more frequently females. IgM MGUS was more frequent in patients with motor CIDP than in patients with typical CIDP. Conclusions: Comorbidities are frequent in patients with CIDP and in almost 50% of them have an impact on treatment choice. Diabetes, MGUS and other immune diseases are more frequent in patients with CIDP than in the general population. Only diabetes seems, however, to have an impact on disease severity and treatment response possibly reflecting in some patients a coexisting diabetic neuropathy.